History and leadership the nature and role of the past in navigating the future - Blincoe, Mark E.; Shoup, John R. (New York, NY : Routledge, 2023)
"Leaders and managers are rightly tasked to take their organizations and communities to a desired future. They are expected to be forward looking with compelling vision statements. As a result, they are often too busy in the present managing the future to be bothered with the past. Yet it is organizational histories that provide the contexts and clues for the future. History and Leadership: The Nature and Role of the Past in Navigating the Future demonstrates that intentional historical perspective-taking provides a sort-of wisdom for doing business in the present and future and equips leaders to leverage the past to help their organizations thrive. This book appeals to several audiences. It will serve as a supplementary text for undergraduate and graduate students in both the humanities and leadership studies. The book also appeals to practicing leaders and managers who wish to develop their emotional, cultural, and social intelligence by exploring perennial issues and lessons found in well-developed histories. This book also serves as a stand-alone read for a range of professionals who want a more recreational and non-traditional read on history and leadership. The book cultivates an appreciation for history and equips readers to be connoisseurs of history for the betterment of themselves and society"--
Preface Chapter 1 -- The Nature and Role of History in the Humanities and Leadership Studies Chapter 2 -- The Renaissance, Enlightenment, and Industrial Revolution Chapter 3 -- A Brief History of Leadership and Organizational Studies Chapter 4 -- History and Contemporary Lessons for Leaders Chapter 5 -- Organizational Histories: Using the Past to Navigate the Future
Keywords: Leadership; Management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Corporate & Business History; BUSINESS & ECONOMICS / Management